2007
DOI: 10.4102/sajp.v63i3.139
|View full text |Cite
|
Sign up to set email alerts
|

The views of patients with spinal cord injuries on their rehabilitation experience

Abstract: Q u a l i t a t i v e R e s e a r c h

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…As, Metabing et al referred in a study to dependence-induced suffering as one of the themes extracted from the experiences of SCI patients. (15) In a qualitative study of SCI patients, they felt physical fatigue over time and were forced to become dependent (Bodil Bjornshave Noe et al (2014). (8) Also, Hosseini Golafshani et al (2013) stated that the first years of SCI is very difficult and challenging, such as the arrival of a person into a new world they had not previously imagined, and are completely dependent on others in this new world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As, Metabing et al referred in a study to dependence-induced suffering as one of the themes extracted from the experiences of SCI patients. (15) In a qualitative study of SCI patients, they felt physical fatigue over time and were forced to become dependent (Bodil Bjornshave Noe et al (2014). (8) Also, Hosseini Golafshani et al (2013) stated that the first years of SCI is very difficult and challenging, such as the arrival of a person into a new world they had not previously imagined, and are completely dependent on others in this new world.…”
Section: Discussionmentioning
confidence: 99%
“…(16) Concerning emotional suffering, the results of Metabing et al's qualitative study suggest emotional experiences including guilt, loneliness, frustration, and futility in SCI patients. (15) In a qualitative study on men with physical and motor injuries, Ardani et al showed that participants had a sense of inferiority, feeling like a burden, and being futile due to being financially dependent on their family. (17) In confirming the physical suffering of SCI patients, Sedghi Gouy Aghaj et al write that pain is the worst and most debilitating problem among SCI patients as they may experience one or more types of pain at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Personal psycho-emotional factors may also affect RHD and functioning after discharge. Mothabeng et al ( 2007 ) emphasised that PWSCI need to address emotions related to the injury and the effects of these emotions on social and family relationships.…”
Section: Introductionmentioning
confidence: 99%